Communication Through Coherence by Means of Cross-frequency Coupling. (21st November 2020) - González, Joaquín; Cavelli, Matias; Mondino, Alejandra; Rubido, Nicolás; BL Tort, Adriano; Torterolo, Pablo
Graphical abstract: Highlights: CTC and CFC have independently been suggested to underlie neuronal communication. CTC relies on phase synchrony and CFC on the interaction between fast and slow rhythms. We designed a method to evaluate fast frequency synchrony modulation by slow rhythms. Theta phase modulates inter-hemispheric fast gamma synchrony during REM sleep. CTC and CFC may be part of the same mechanism for large-scale brain communication. Abstract: The theory of communication through coherence (CTC) posits the synchronization of brain oscillations as a key mechanism for information sharing and perceptual binding. In a parallel literature, hippocampal theta activity (4–10 Hz) has been shown to modulate the appearance of neocortical fast gamma oscillations (100–150 Hz), a phenomenon known as cross-frequency coupling (CFC). Even though CFC has also been previously associated with information routing, it remains to be determined whether it directly relates to CTC. In particular, for the theta-fast gamma example at hand, a critical question is to know if the phase of the theta cycle influences gamma synchronization across the neocortex. To answer this question, we combined CFC (modulation index) and CTC (phase-locking value) metrics in order to detect the modulation of the cross-regional high-frequency synchronization by the phase of slower oscillations. Upon applying this method, we found that the inter-hemispheric synchronization of neocortical fast gamma during REM sleep depends on the instantaneous phase of the theta rhythm. These results show that CFC is likely to aid long-range information transfer by facilitating the synchronization of faster rhythms, thus consistent with classical CTC views.